Invasive frontal mucocele: benign but agressive - García Oriola, Guillermo; Quilis- Quesada, Vicent; Vega Torres, Esteban; Irles Vidal, Carlos; González Darder, José Manuel (Revista Argentina de Neurocirugía, 2022)
Paranasal sinus osteomas are slow growing, benign tumors usually asymptomatic and incidentally diagnosed. Existence of obstruction in the sinus drainage holes seems to be the key in the formation of mucoceles. They usually have a local growth, but if intracranial invasion occurs due to rupture of the internal wall of the frontal sinus, secondary neurological symptoms and complications may appear. Early diagnosis and treatment marks the evolution in these cases, and determines the associated morbimortality. We present and describe the surgical management step by step of the case of a 61-year-old patient with a frontal intrasinusal osteoma with mucocele and secondary intracranial invasion that presented the onset of generalized tonic-clonic seizures.